Evaluating the Impact of Maternal Vitamin D Supplementation on Sow Performance, Serum Vitamin Metabolites, Neonatal Muscle and Bone Characteristics, and Subsequent Pre-weaning Pig Performance - J. R. Flohr; J. C. Woodworth; M. D. Tokach; S. S. Dritz; R. D. Goodband; J. M. DeRouchey; J. R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 56 gestating sows (PIC 1050; 35-d post-insemination) were used in a 30-d trial to determine the serum 25(OH)D3response to increasing concentrations of vitamins D3. At initiation, sows were randomly allotted to 1 of 7 dietary vitamin D3treatments (91, 363, 726, 1,451, 2,903, 5,806, or 11,612 IU of vitamin D3/lb of complete diet) with 8 sows per treatment. All sows were fed 5.5 lb daily at 0800. Increasing vitamin D3 increased (quadratic; P<0.001) serum 25(OH)D3with the response depicted by the following prediction equation: Serum 25(OH)D3,ng/mL = 35.1746 + (0.002353 × dietary vitamin D3, IU/d) - (0.0000000156 × dietary vitamin D3, IU/d2) In Exp. 2, 112 sows and their litters were used to determine the effects of supplemented vitamin D on sow performance, subsequent pre-weaning pig performance, neonatal pig bone and muscle characteristics, and serum vitamin metabolites. Sows were allotted to 1 of 4 dietary regimens: 1) low vitaminD3(363 IU/lb); 2) medium vitamin D3(907 IU/lb); 3) high vitamin D3(4,354 IU/lb); or 4) 23μg 25(OH)D3/lb (Hy-D, DSM Nutritional Products Inc, Parsippany, NJ), which were fed throughout gestation and lactation. There were 25 to 27 sows per treatment. Overall, increasing maternal vitamin D3increased (linear, P = 0.001) serum 25 (OH)D3 of sows on d 100 of gestation, at farrowing, and at weaning. Also increasing vitamin D3in diets fed to sows increased piglet serum 25(OH)D3at birth (linear, P = 0.001) and weaning (quadratic, P = 0.033). Sows fed 25(OH)D3had greater (P<0.001) serum 25(OH)D3concentrations on d 100 of gestation, at farrowing, and at weaning compared to sows fed the low or medium concentration of vitamin D3; however, they were reduced (P<0.004) compared to the serum 25(OH)D3concentrations of sows fed the high concentration of vitamin D3on the same collection days. Piglets from sows fed 25(OH)D3had greater serum 25(OH)D3compared to piglets from sows fed the low and medium concentration of vitamin D3; however, at weaning, serum 25(OH)D3concentrations were only greater compared to the low concentration of vitamin D3. Also, piglets from sows fed the high concentration of vitamin D had greater (P = 0.011) serum 25(OH)D3concentration at birth and at weaning, compared to piglets from sows fed 25(OH)D3. Maternal performance, litter characteristics, neonatal bone ash content, and neonatal muscle fiber characteristics were largely unaffected by the maternal vitamin D regimen. Overall, vitamin D3and 25(OH)D3both appear to be useful at increasing serum 25(OH) D3concentrations, but more vitamin D3(on an IU basis) is needed to achieve similar serum 25(OH)D3responses compared to feeding 25(OH)D3. Interestingly, sows fed 25(OH)D3in lactation had less vitamin D transport to the pig than sows fed medium and high concentrations of vitamin D3suggesting that vitamin D3is still a more useful metabolite for milk transfer of the vitamin. Due to the lack of impact of maternal vitamin D regimen on sow or pre-weaned pig performance, and neonatal muscle characteristics, more research examining the impact of vitamin D on immune function and novel biological processes is needed to assess the value of vitamin D supplementation strategies in pigs.
Keywords: 25(OH)D3; sow nutrition; vitamin D